The simplified approach for estimating probabilistic safety factors in fracture mechanics. (November 2020) - Matvienko, Yu.G.
Highlights: Safety factor against collapse is employed to estimate safety factors against fracture. Correlation of the safety factor against collapse with safety factors against fracture is predicted. The probability of failure as a function of the safety factor against collapse is estimated. The effect of the failure probability on the safety factor in fracture mechanics is analyzed. Abstract: Basic principles of the simplified probabilistic approach in structural integrity assessment are proposed to estimate probabilistic safety factors against fracture. The coefficients of variation for the material resistance are assumed to be the same independently on modes of failure and the resistance effects, namely, fracture or plastic collapse. The load for engineering components under consideration is assumed to be described by the stochastic distribution independently on modes of failure. In this case, probabilistic safety factor against collapse can be employed to estimate safety factors against fracture taking into account correlation of the safety factor against collapse in terms of the yield stress with safety factors against fracture in terms of the fracture toughness or the failure assessment diagram. Thus, safety factors against fracture calculated by this simplified method can be considered as probabilistic safety factors. The probability of failure as a function of the safety factor against collapse is estimated by means of the reliability index β calculated for representative combinations of the coefficients of variation (COV). The effect of the failure probability on the safety factor against fracture in terms of the fracture toughness and the failure assessment diagram for representative combinations of the values COV is analyzed. This approach will allow avoiding more complex and costly probabilistic analysis of failure for fracture based on the fracture toughness distribution.